Comparison of real-time reverse transcriptase–polymerase chain reaction and nested or commercial reverse transcriptase–polymerase chain reaction for the detection of hepatitis E virus particle in human serum - Ahn, Jeong-min; Rayamajhi, Nabin; Gyun Kang, Sang; Sang Yoo, Han (Diagnostic microbiology and infectious disease, 2006)
Hepatitis E virus (HEV) was originally identified as the causative agent of enterically transmitted non-A, non-B hepatitis. The virus is the 7.5-kb single-stranded positive RNA virus and has been classified in the genus Herpesvirus of the family Herpesviridae. Recently, HEVs were identified from several countries worldwide from human and animals including swine. Studies on the genomic analysis of HEV isolates and seroprevalence of anti-HEV antibodies suggested that HEV has been considered as a potent zoonotic agent. The HEV infection has been diagnosed by detection of anti-HEV antibodies or virus by using reverse transcriptase–polymerase chain reaction (RT-PCR) methods in the blood or feces. However, these diagnostic methods were not quantitative and not enough to diagnose small amounts of target molecules. Moreover, these methods were not adequate during the incubation period or early acute phase. To overcome these problems, real-time RT-PCR method was developed with a cloned viral DNA and in vitro transcribed cRNA in this study. The sensitivity of the reaction was 1.68 × 10 1 copies per reaction. Correlation coefficient values of the reactions in the repeated experiments were over 0.99. Ranges of slopes and coefficient variation values were from 3.341 to 3.435 and from 1.20 to 5.98, respectively. In comparison of the real-time PCR with nested or commercial RT-PCR, HEV particles could be detected in the negative samples, which were determined by conventional nested RT-PCR.